Vallejo Welcomes Golden Bear Home from Mercy Trip - Unknown (Unknown)
A favorable tide speeded the Golden Bear home to the California Maritime Academy dock at Morrow Cove where nearly 1,000 Vallejoans yesterday afternoon welcomed the stately training ship at the conclusion of her 20,000 mile cruise as a mercy vessel for thousands of hungry Europeans. The ship "like a thoroughbred returning to its stable," arived here at 4:30 p.m. one-half hour ahead of schedule in the last leg of its long jaunt. The Golden Bear left Pier 7 in San Francisco at 2 p.m.